2020
DOI: 10.3847/1538-4357/abc55b
|View full text |Cite
|
Sign up to set email alerts
|

Why Interstellar Ice Dust Grains Should Be Elongated

Abstract: Models of interstellar dust alignment assume that dust grains are elongated, but none of these models explain why dust grains should be elongated. On the other hand, models of interstellar dust grain growth assume that dust grains are spherical and not elongated. We show that when dusty plasma effects and the dipole moment of water molecules are together taken into account, ice grains in interstellar space should be prolate ellipsoids and not spheres. Dusty plasma analysis shows that an ice grain is charged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…It is thus highly likely that the rapid homogeneous nucleation observed in the Caltech water ice experiment occurs in the sequence: formation of weakly ionized plasma (free electrons and ions in a sea of neutrals), dissociation of water into hydroxyl and hydrogen atoms, negative ion formation, hydrate on negative ion, growth of hydrate to macroscopic ice grain. Because of continuous electron and ion bombardment with electron flux exceeding ion flux, the ice grain will become increasingly negatively charged in the usual dusty plasma sense (Bellan 2020) as it becomes larger and so will continue to attract water molecules and grow.…”
Section: Classic Nucleation Theory Summarizedmentioning
confidence: 99%
“…It is thus highly likely that the rapid homogeneous nucleation observed in the Caltech water ice experiment occurs in the sequence: formation of weakly ionized plasma (free electrons and ions in a sea of neutrals), dissociation of water into hydroxyl and hydrogen atoms, negative ion formation, hydrate on negative ion, growth of hydrate to macroscopic ice grain. Because of continuous electron and ion bombardment with electron flux exceeding ion flux, the ice grain will become increasingly negatively charged in the usual dusty plasma sense (Bellan 2020) as it becomes larger and so will continue to attract water molecules and grow.…”
Section: Classic Nucleation Theory Summarizedmentioning
confidence: 99%
“…Grains acquire electric charge from this ambient plasma, as first noted by Spitzer (1941), because electrons have a higher collision frequency with the grains than do ions and so are collected by grains more frequently. The charge can affect ice grain formation (Bellan 2022), agglomeration (Ivlev et al 2015), accretion of water molecules (Bellan 2020), and dynamics (Mitchell et al 2006;Mendis & Horányi 2013). Ice grain nucleation has traditionally been assumed to be heterogeneous, i.e., the grain forms as an ice coating on a non-ice nucleus, which is typically carbon or silicate.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have reported the nonspherical dust particles with DAWs [1,24]. Because dust grains existing in naturally occurring plasmas are likely to be nonspherical [25], it is beneficial to study the DAWs with nonspherical dust grains.…”
Section: Introductionmentioning
confidence: 99%